Effects of tualang honey on cognitive performance among patients with schizophrenia in Hospital Universiti Sains Malaysia, Kelantan - Rosliza Yahaya
Introduction: Cognitive impairment in schizophrenia, including deficits in working memory, verbal learning and memory, predate the onset of frank psychosis and are stable throughout the course of the illness in most patients. Recently, tualang honey (TH) has been shown to improve immediate memory in postmenopausal women and rats. Objectives: The aim of this study was to investigate the effect of TH supplementation, on verbal learning and memory (VLM) in schizophrenia patients. Methods: A total of 80 schizophrenia in outpatient Psychiatric Clinic, Hospital Universiti Sains Malaysia, Kelantan were recruited between August-December 2014 and randomly assigned to two groups: TH (20mg/d) and untreated control. Their VLM performances were assessed using the Malay version of the Auditory Verbal Learning Test (MVAVLT) before (week 0) and after (week 8) of intervention. Repeated measures analysis of covariance control for age, education and duration of illness was done using PASW version 20.0. Result: A total of 28 subjects completed the study (TH group=17, control group=11). There were no significant differences in socio-demographic characteristics between the subjects in TH and control group except for number of admission. The mean total learning and delayed recall within each group based on time were significant with F=5.86, p=0.023 and F=5.15, p=0.0.32, respectively when controlled for covariate age. However, there was no significant difference in TH group. There were no significant difference of mean total learning and delayed recall from between group factor analyses with p=0.299 and control group p=0.536 respectively. The mean total learning and delayed recall within each group based on time were not significantly different with F=0.19, p=0.671 and F=0.55, p=0.465 respectively when controlled for covariate education. There were no significant differences of mean total learning and delayed recall from between group factor analyses with p=0.326 and p=0.528 accordingly. Subsequently, the mean total learning within each group based on time was no significant difference with F=1.27, p=0.271 when controlled for covariate duration of illness. Even though, mean delayed recall was significant with F=7.05, p=0.013, there was no significant mean difference in TH group. There were no significant differences of mean total learning and delayed recall from between group analyses with p=0.375 and p=0.544 correspondingly. There were no significant differences in total learning and delayed recall score between TH and control groups based on time when controlled of covariates; age, education and duration of illness. Conclusions: Schizophrenia subjects who receive TH supplementation for 8 weeks did not show significant improvement in the total learning (immediate memory/STM) and delayed recall (LTM) compared to control group.